Peran Corporate Governance Dan Esg Dalam Meningkatkan Reputasi Dan Keberlanjutan Perusahaan : Studi Literatur - Fani, Rista Adhalia; Marsha, Indy Melva Adinda; Putri, Nifta Ardilia; Pradanti, Alsya Puteri; Sari, Ayu Novita (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2025)
The era of globalization requires companies to implement Good Corporate Governance (GCG) and Environmental, Social, and Governance (ESG) as a comprehensive strategy in achieving the desires of modern organizations. This research aims to analyze the role of Good Corporate Governance and ESG in improving reputation and improving companies through a comprehensive approach. The research uses a qualitative descriptive method with Systematic Literature Review (SLR), collecting and analyzing data from journals, and related literature. The findings show that effective implementation of Good research Corporate Governance can increase stakeholder trust, optimize performance and create sustainable value. ESG integration helps companies identify risks, build a positive reputation, and gain better access to capital. Good Corporate Governance and ESG are fundamental strategic instruments in creating a sustainable business ecosystem, improving reputation, and ensuring the company's competitive advantage in the global era.